2022
DOI: 10.4266/acc.2022.00395
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and timing of mortality in children dying in pediatric intensive care: a 5-year experience

Abstract: Background: Pediatric intensive care units (PICUs), where children with critical illnesses are treated, require considerable manpower and technological infrastructure in order to keep children alive and free from sequelae. Methods: In this retrospective comparative cohort study, hospital records of patients aged 1 month to 18 years who died in the study PICU between January 2015 and December 2019 were reviewed. Results: A total of 2,781 critically ill children were admitted to the PICU. The mean±standard devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…In the same study, multiorgan failure and cardiac diseases were common causes in patients who died early. 30 Another recent study reported sepsis and septic shock as the common cause of early decedents. 31 So, our study findings are in line with the recent literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, multiorgan failure and cardiac diseases were common causes in patients who died early. 30 Another recent study reported sepsis and septic shock as the common cause of early decedents. 31 So, our study findings are in line with the recent literature.…”
Section: Discussionmentioning
confidence: 99%